TINJAUAN YURIDIS SOSIOLOGIS PENERAPAN REHABILITASI TERHADAP PECANDU DAN KORBAN PENYALAHGUNAAN NARKOTIKA OLEH BADAN NARKOTIKA NASIONAL KABUPATEN SIDOARJO - Alriza Nurul Ambiya (Dinamika, 2019)
ABSTRACT     In the general problems effect of narcotics is very bad for health and social impact. The victims of narcotics will assume psychology and social burden. Agording to practice experience’s people who consume the narcotics starts from social influence.     In this problem the consumens of narcotics and dealers of narcotics has a thin differents mean. Subtance of narcotics that formely showed for medicine, with develope of knowledge and thecnology the kind of narcotics can be prossesed with so many ways and can be misused of hat function.     The level of surveillance and control as effort for wipe out and prevent misused and dark dealers of narcotics very needed. Because the crime in this problem is growing from the kuantity and kuality side. That’s why misused of the narcotic must be get the maintance medical and social. Where in the victims and his family must be make report in order to get a development, surveillance and rehabilitation effort in the medical center, hospital or medical rehabilitation and social rehabititation.